2009
DOI: 10.1080/00952990903075034
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Impulsivity and High Risk Sexual Behaviors in Dually Diagnosed Outpatients

Abstract: Background/Objectives-It is unknown whether impulsivity is associated with risky sexual behavior in dually diagnosed clients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 20 publications
(29 reference statements)
2
23
0
2
Order By: Relevance
“…In addition to the direct risks of substance use, homeless youth who use substances are more likely to experience mental health sequelae, such as depression and anxious coping, and engage in other highrisk behaviors [78,86,87]. This, in turn, puts them at risk for various health problems.…”
Section: Substance Usementioning
confidence: 95%
See 1 more Smart Citation
“…In addition to the direct risks of substance use, homeless youth who use substances are more likely to experience mental health sequelae, such as depression and anxious coping, and engage in other highrisk behaviors [78,86,87]. This, in turn, puts them at risk for various health problems.…”
Section: Substance Usementioning
confidence: 95%
“…This, in turn, puts them at risk for various health problems. Specifically, individuals who engage in IDU are at increased risk for contracting HIV [86,87]. Substance use also increases the likelihood that individuals will engage in risky sexual behaviors.…”
Section: Substance Usementioning
confidence: 98%
“…Delay discounting is a putative measure of impulsivity (Johnson & Bickel, 2002;Madden, Begotka, Raiff, & Kastern, 2003), with higher discounting rates indicating more impulsivity. Importantly, delay discounting like perfectionism, has been associated with depression and eating disorders, including high levels of BED (Black, Serowik, & Rosen, 2009;Davis, Patte, Curtis, & Reid, 2010;Lempert & Pizzagalli, 2010;Takahashi et al, 2008). For example, Davis et al (2010) found that women with BED and individuals who were obese discounted at high rates on discounting measures, indicating that the ability to delay gratification may influence eating behaviors.…”
Section: Introductionmentioning
confidence: 94%
“…Some have argued, however, that this association reflects impulsive personality traits that lead someone to take risks rather than an intoxication syndrome per se (Hayaki et al 2006;Winters et al 2009). Indeed, impulsivity is common to those with psychiatric disorders and has been associated with sexual risk behavior (Black et al 2009). Consequently, substance use and impulsivity should be examined as possible risk factors for unprotected sex.…”
Section: Introductionmentioning
confidence: 98%